Structural identification of the multidimensional object according to the actual experiment - Блохін, Л. М.; Держак, С. В. (Proceedings of National Aviation University (archive), 2002)
The problem of structural identification of the dynamics of a multidimensional object is consideredgives an opportunity to compile the basic provisions of the methodology for calculating optimal estimatesthe dynamic characteristics of the multidimensional object and the external object acting on itperturbation according to the experiment in normal operating modes.